Accountability systems and instructional approaches in youth volleyball training - Pereira, F.; Mesquita, I.; Graca, A. (Journal of Sports Science & Medicine, 2009)
The purpose of this study was to examine accountability systems operating in youth volleyball training sessions and to understand how those systems vary according to the instructional tasks and the nature of the information provided by coaches. Additionally, the interactive effect of the players' age group on accountability systems and instructional tasks will be inspected. Twenty-eight youth volleyball coaches (for under 14s and under 18s) were observed, one training session each. Systematic observation strategies were used to describe and analyse task presentation and task structure during practice. Results convey that the accountability systems implemented by coaches were mainly implicit and governed by opportunity rather than explicit performance criteria imparted in task presentation. Remarks on the quality of performance only occurred during ongoing practice. More often than not coaches showed no reaction when athletes did not accomplish the tasks, failing to convey consequential expectancy-demand-monitoring messages. The instructional approach was predominantly composed of informing tasks, of technical nature and general information, which can reflect a technique and generalist coach profile. These results indicate the presence of weak and ambiguous accountability system, also corroborated by positive correlations of extending tasks with the category without exigency task presentation as well as with no reaction to unaccomplished tasks. There were no notorious differences in accountability behaviours between players' age group.